Relationship between Clinicopathological Factors of Breast Cancer and Lymph Node Metastasis in Young Women - Halim, Zuvar Faza; Kartini, Diani (South Eastern European Journal of Public Health, 2024)
Aim : To determine the incidence of lymph node metastasis in breast cancer of young women and its relationship with clinicopathologic factors. Methods : The study used an analytic observational design and a cross-sectional approach. Bivariate analysis was performed with Fisher's exact probability test to determine the association of clinicopathologic factors with lymph node metastasis. Results: N1 lymph node metastases could be found in most of the young women breast cancer patients at 42.9%, followed by N3 and N2 at 11.4% and 8.6%, respectively. On the other hand, 37.1% of patients showed no lymph node metastasis. Fisher's exact probability test showed that of the six clinicopathological factors, only tumour size was associated with lymph node metastasis with a p-value of 0.031. Conclusion : The incidence rate of lymph node metastasis in breast cancer of young women was 42.9% for N1, 11.4% for N3, and 8.6% for N2. There was a significant association between tumour size and lymph node metastasis.